On the relationship between Scandinavian extreme precipitation days, atmospheric blocking and Red Sea coral oxygen isotopes. (29th July 2022) - Rimbu, Norel; Felis, Thomas
Abstract: In the context of ongoing climate change towards a warmer world, it is important to gain insights into the frequency and intensity of weather and climate extreme events over longer periods of time prior to the start of instrumental observations. Reconstructions of their variability are usually hampered by the rareness of natural archives for the pre-instrumental period that document climate variability at a sub-seasonal resolution. A potential archive for extreme events are annually banded reef corals which incorporate isotopic proxies of temperature and hydrology into their carbonate skeletons at sub-seasonal resolution, grow for centuries, and overlap with the observational period. Here, we investigate the relationship between the frequency of heavy precipitation days in southwestern Scandinavia and colder conditions in the northern Red Sea during winter, as documented by a coral oxygen isotope record from the northernmost area of tropical reef growth in the European sector of the Northern Hemisphere. Statistical analysis of observational data reveals that cold conditions in the northern Red Sea are associated with an increased frequency of heavy precipitation in southwestern Scandinavia. From a synoptic-scale perspective, this teleconnection can be explained by winter atmospheric blocking over mid-latitude Europe, which is a large-scale pattern of atmospheric pressure that can be active for several days or weeks. We show that increased winter blocking activity in the European region is related to an increased frequency of extreme moisture transport by atmospheric rivers affecting southwestern Scandinavia, as well as to an increased meridional advection of cold continental air from the north towards the subtropical northern Red Sea. The coral-based Scandinavian heavy precipitation reconstruction shows strong decadal variations during the pre-instrumental period. Our results provide insights into the frequency of winter atmospheric blocking events and related daily precipitation extremes in the European region, as well as into the impact of mid-latitude climate extremes on coral reef ecosystems in the northern Red Sea, during the last centuries.